CARL GUSTAV JUNG'S CONCEPT OF COLLECTIVE UNCONSCIOUS AND ARCHETYPE - Karakaş, Ülkem; Karaaziz, Meryem (International Scientific Journal Vision, 2024)
Carl Gustav Jung, the founder of the analytical psychology, is one of the leading figures in the field of psychology.Jung points out that the behaviors, feelings and thoughts that people show are not only based on the individual's own experiences or past experiences, but perhaps behind them there may be feelings, thoughts, behaviors or an inner instinct inherited from the individual's ancestors.Jung used the terms psyche and psyche (psychic) when talking about the structure and activities of the mind in his studies. According to the psyche, the mind is divided into consciousness and unconscious. The unconscious is analyzed in two sub-dimensions: the personal unconscious and the collective unconscious. The personal unconscious consists of complexes and the collective unconscious consists of archetypes.In this study, C.G. Jung's work on analytical psychology, concepts and theories are analyzed and compiled.